Akademiliv - Språkbanken Text (University of Gothenburg, 2025)
Akademiliv is the Sahlgrenska Academy’s staff magazine online.

Akademiliv är Sahlgrenska akademins personaltidning på nätet.
Akademiliv
Keywords: Language Technology (Computational Linguistics); magazines; news texts; non-fiction; corpus; Natural Language Processing; Språkbehandling och datorlingvistik